ANALYZING PROGRAMMING LANGUAGE GENTEE WITH C LANGUAGE (Case Study APPLICATION PROGRAM N FAKTORIAL) - Yusnitasari, Tristyanti; Umniati, Naeli; Deni, Deni (Jurnal Ilmiah Informatika Komputer, 2009)
Nowadays, the development of programming language given rise to the creation of new software which includes application, operating system and programming language. Programming language Gentee is one of the new programming language where its features and structures similar to C language.Gentee was developed based-on C library and has a procedural characteristics. This research was conducted to compare between C language and Gentee. Gentee may be used for the development of standard application as well as web-based application. In this paper, application of factorial computation was developed as a target application for the comparison.Keyword(s): Gentee language, C language, Procedural, Application, Factorial.Subject Description : D.2.Software Engineering | D.2.8.Metrics | Performance Measures